Accessibility to educational facilities in big cities- a field study on the cities of Beni Mellal and Al- Faquih ben Saleh – Morocco - Abdelhak, Ahandar; Mohammed, Mayoussi; Mohammed, El- Assaad (Journal of Humanities & Social Sciences, 2020)
This article treats the topic of accessibility to educational facilities in Morocco’s biggest cities. Two key concepts organize the take a look at accessibility and educational facilities. The research targets to solution the subsequent difficult question: What is the link among accessibility to educational facilities and their distribution? Is it within geographical distance, temporal distance, or type of facilities or with socio- demographic data? The answer to this question requires the following targets to be achieved: To investigate the degree of homogeneity or distinction within the distribution of educational facilities. This explains the adoption of the statistical hypothesis: "There is not any statistically significant distinction (H0) inside the accessibility of educational facilities, in keeping with the bodily characteristics of accessibility (time, distance and transport system) and intermediate variables (age, sex, stage of education, geographical foundation and profession). Data collect was primarily based on two methods: the primary is an approach theoretical(administrative data), the second one based at the field, through selecting the most suitable stratified sample, thinking of the spatial weighting of the facilities and the dimensions of the city population (by way of 40%), for a complete of 313 households. Data evaluation additionally involves the use of statistical measures. They extensively utilized mapping tools (descriptive and explanatory). The study revealed several results: Firstly: differentiated distribution of educational facilities, we also find a difference in accessibility according to distance and time, with the center being dominated by the most of its facilities, giving it a preference for accessibility over than peripherals. Second, among the socio- demographic variables controlling access, we find that the variables of age, education level, occupation and means of transport are independent of the respondents’ attitudes, in relation to gender and geographical origin